Posterior scleral reinforcement for the treatment of pathological myopia - Li, Xiu-Juan (Int J Ophthalmol, 2016)
AIM: To investigate the effects of posterior scleral reinforcement (PSR) in the treatment of pathological myopia. METHODS: The study included 52 eyes in 43 patients with pathological myopia who underwent PSR (PSR group), and 52 eyes in 36 age- and myopia-matched patients who did not undergo such treatment as control group. Axial length, refraction error, best corrected visual acuity (BCVA), and macular scans by optical coherence tomography (OCT) were recorded at baseline, 6mo, 1, 3 and 5y after the surgery, and the complications were noted. RESULTS: There were no statistical differences in axial length, refractive error, or BCVA between the PSR group and the control group at baseline. At the end of the follow-up, the mean axial length was 29.79±1.26 mm in the PSR group, which was significantly shorter than that in the control group (30.78±1.30 mm) (P<0.01), and the mean refractive error was -16.86±2.53 D in the PSR group, which was significantly lower than that in the control group (-19.18±2.12 D) (P<0.01). A statistically significant difference in BCVA was found between the PSR group (0.51±0.25 logMAR) and the control group (0.62±0.26 logMAR) at the postoperative 5-year follow-up (P<0.01). There were no serious complications during the 5-year follow-up period. CONCLUSION: PSR can prevent axial elongation and myopia progression in eyes with pathological myopia.